2019
DOI: 10.1242/jeb.202580
|View full text |Cite
|
Sign up to set email alerts
|

The photon menace: kleptoplast protection in the photosynthetic sea slugElysia timida

Abstract: Absorption of excessive light by photosymbiotic organisms leads to the production of reactive oxygen species that can damage both symbiont and host. This is highly relevant in sacoglossan sea slugs that host functional chloroplasts 'stolen' from their algal foods (kleptoplasts), because of limited repair capacities resulting from the absence of algal nuclear genes. Here, we experimentally demonstrate (i) a hostmediated photoprotection mechanism in the photosynthetic sea slug Elysia timida, characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Similar data has previously been presented from E. timida and also E. chlorotica(Cruz et al, 2015;Christa et al, 2018). Higher level of NPQ in the slugs is likely linked to the strong acidification of the lumen in the slugs (Figure 4A), since the major qE component of NPQ is pH dependent(Müller et al, 2001; Papageorgiou and Govindjee, 2014).The xanthophyll cycle of freshly fed E. timida is functional(Cartaxana et al, 2019), but it is unclear whether the NPQ induced already during the first 100 s of the RLC measurement (Figure 5G) is due to lumen acidification switching on the xanthophyll cycle, or whether lumen acidification directly enhances quenching capacity at the level of light harvesting antennae. Nevertheless, strong NPQ has obvious benefits for chloroplast longevity in E. timida.Flavodiiron proteins function as alternative electron sinks in E. timida and Acetabularia E. timida and Acetabularia utilize oxygen-dependent electron acceptors of PSI during dark-to-light transition, but their functionality is weaker in E. timida (Figure 4B-C).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Similar data has previously been presented from E. timida and also E. chlorotica(Cruz et al, 2015;Christa et al, 2018). Higher level of NPQ in the slugs is likely linked to the strong acidification of the lumen in the slugs (Figure 4A), since the major qE component of NPQ is pH dependent(Müller et al, 2001; Papageorgiou and Govindjee, 2014).The xanthophyll cycle of freshly fed E. timida is functional(Cartaxana et al, 2019), but it is unclear whether the NPQ induced already during the first 100 s of the RLC measurement (Figure 5G) is due to lumen acidification switching on the xanthophyll cycle, or whether lumen acidification directly enhances quenching capacity at the level of light harvesting antennae. Nevertheless, strong NPQ has obvious benefits for chloroplast longevity in E. timida.Flavodiiron proteins function as alternative electron sinks in E. timida and Acetabularia E. timida and Acetabularia utilize oxygen-dependent electron acceptors of PSI during dark-to-light transition, but their functionality is weaker in E. timida (Figure 4B-C).…”
supporting
confidence: 76%
“…Photoprotective mechanisms counteract photodamage. Recent efforts have advanced our understanding of photoprotection in kleptoplasts (Christa et al, 2018;Cartaxana et al, 2019). It has been shown that kleptoplasts of E. timida do retain the capacity to induce physiological photoprotection mechanisms similar to the ones in the prey green alga Acetabularia acetabulum (hereafter Acetabularia) (Christa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 3 Photoprotective mechanisms counteract photodamage. Recent efforts have advanced our 42 understanding of photoprotection in kleptoplasts (Christa et al, 2018;Cartaxana et al, 2019). It has 43 been shown that kleptoplasts of E. timida do retain the capacity to induce physiological photoprotection 44 mechanisms similar to the ones in the prey green alga Acetabularia acetabulum (hereafter Acetabularia) 45 (Christa et al, 2018).…”
Section: Introduction 19mentioning
confidence: 99%
“…The most obvious threat for these ‘solar-powered’ sea slugs are reactive oxygen species (ROS), which are formed by the addition of electrons to oxygen: these reactive molecules can severely damage tissues and eventually cause cell death ( Dorrell and Howe, 2012 ). Complex compounds that block oxidation (the loss of electrons) and mechanisms for dissipating excessive energy have both been proposed to play a protective role in kleptoplast-bearing sea slugs ( Cartaxana et al, 2019 ; Torres et al, 2020 ). However, despite over 50 years of research, it is still unclear how kleptoplasts are maintained in animal cells.…”
mentioning
confidence: 99%